2011
DOI: 10.1185/03007995.2011.590968
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of premature ejaculation and barriers to its recognition and treatment

Abstract: Conclusions drawn from this review are limited due to inherent variations across studies, including criteria to define PE, study designs, outcome measures, populations, survey instruments, and study settings. While the psychological distress associated with PE suggests the appropriateness of at least minimal counseling for couples, limited data are available to support a combined psychotherapeutic and pharmacologic treatment approach. The paucity of well-designed psychotherapy or combination studies represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…It has been shown in previous studies that sexual dysfunction relates to a wide series of psychological problems, such as general anxiety and depression (Althof, ; Gao et al, , ; Hale & Strassberg, ; Rowland, ; Rowland & Cooper, ; Zhang et al, ). An observational study (Limoncin et al, ) (using the orgasmometer) conducted in Rome showed that men affected by premature ejaculation perceived significantly lower orgasmic intensity than sexually healthy men.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in previous studies that sexual dysfunction relates to a wide series of psychological problems, such as general anxiety and depression (Althof, ; Gao et al, , ; Hale & Strassberg, ; Rowland, ; Rowland & Cooper, ; Zhang et al, ). An observational study (Limoncin et al, ) (using the orgasmometer) conducted in Rome showed that men affected by premature ejaculation perceived significantly lower orgasmic intensity than sexually healthy men.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Embarrassment and disbeliefs regarding treatment among the patients, improper expertise of health providers and hostile atmosphere in the health institutions has been often implicated in deficiency of treatment seeking behavior among patients of ED. 9,10 As such, a thorough work-up including elicitation of risk factors coupled with necessary laboratory tests and integrated with clinical picture helps to diagnose and develop a treatment plan to manage these patients effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have shown that impaired sexual function in men with PE is significantly associated with a range of negative psychological effects (e.g., anxiety or depression) [7–9]. A cross‐sectional study conducted in Korea showed that men with PE suffered from various psychological problems, including depression, low self‐esteem, anxiety, and low sexual satisfaction.…”
Section: Introductionmentioning
confidence: 99%